dinamika dan harmonisasi hubungan antara kebijakan kepala desa dan badan perwakilan desa - Moch Fairuz Fahrezi Al-Haibah; Samuji Samuji (JOURNAL SAINS STUDENT RESEARCH, 2025)
In order to be accessible, the implementers and administrators of village government cannot be separated from the human resources of the village apparatus. It is an important component of government management that cannot be interpreted in a double way and ironically goes hand in hand with higher regulations. Because it is autonomous, the implementation of government is formed by an autonomous community. Therefore, the formulation of the preparation of laws and regulations must be orderly. This study aims to answer a number of problems, including the challenges faced by village officials in preparing draft legislation. The purpose of preparing draft legislation is to measure the basis for preparing legislation and making policies that target local governments. This element then developed into scientific advice which ultimately became a normative approach adopted by the government in the process of drafting legislation. This advice has the potential to become a legal basis for all village agencies.